Meta-Analysis of Forecast Analysis on Stock Price - Evelyn Angela Hananto; Vena Purnamasari (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Analysts' views on economic risk can be an important part of an investor's investment decision-making process. Several researchers have conducted research on analyst forecasts and stock prices. However, we need to look at the consistency of the results of previous studies in order to draw general conclusions. This must be done to prove whether analyst forecasts affect stock prices. The consistency of results in this study was determined using a meta-analysis method. This method is supported by the CMA (Comprehensive Meta-Analysis) software. Meta-analysis provides an estimate of the effect size to measure the relationship between the independent variable (analyst forecast) and the dependent (stock price). The heterogeneity test results show that I-squared is > 50 percent, which means high heterogeneity. The correlation analysis results show a p-value of 0.004, meaning that analyst forecast studies on stock prices are heterogeneous. Heterogeneity refers to differences in data within each study or between major studies. The results in this study are heterogeneous, caused by high sampling error when the research location for each sample is different due to differences in economic conditions. Therefore, analyst forecasts have an effect on stock prices.